Acute effects of static stretching of upper arm and forearm on the accuracy of free throws in basketball - Vuckovic, I.; Gadzic, A. (Acta Gymnica, 2016)
Background: Free throws are a very important element in modern basketball. There are many studies focused on different aspects ranging from variability in the mechanics of throwing at various skill levels to the influence of free throws on the results of games.